Scrapbook containing newspaper clippings, etc. ...
Volume (42 pages) containing miscellaneous clippings, maps, charts, tables, etc., relating to U.S. history, politics, and local events in Maryland and the District of Columbia. Includes material relating to the Revolution, the War of 1812, the War with Mexico, and a list of signatures of citizens of Georgetown (1815). Kept by an unidentified person.
Collection material in English.
Keywords: Commonplace books; Mexican War, 1846-1848.; Georgetown (Washington, D.C.) -- History; Maryland -- History, Local; United States -- History -- Revolution, 1775-1783.; United States -- History -- War of 1812.; Washington (D.C.) -- History